Pemanfaatan Lingkungan Madrasah Sebagai Sumber Belajar Di MI Islamiyah Kota Serang - Habudin Habudin; Ayu Rosdiana Ayu (Lembaga Pengembangan Kinerja Dosen, 2025)
One important variable in improving learning activities and achievements is utilising the madrasah environment as a learning resource. The objectives of this study are 1). To determine the actual conditions of the environment as a learning resource at MI Islamiyyah Kota Serang. 2). To determine the utilisation of the environment as a learning resource at MI Islamiyyah Kota Serang. 3). To identify the supporting and inhibiting factors in utilising the environment as a learning resource at MI Islamiyyah Kota Serang. This study used a qualitative method and concluded that the environment at MI Islamiyah Kota Serang has good learning resources, but teachers have not been able to utilise them optimally, thus requiring assistance from learning media experts.